Studi Eksplorasi Tentang Penyebaran Teknologi Informasi Untuk Usaha Kecil Dan Menengah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT This paper investigates factors contributing to the diffusion and adoption of IT within small and medium-sl=ed firms in Indonesia. Both quantitative and qualitative approaches were used to answer detailed research questions about IT diffusion at the level of the firm Bused on the exploratory nature of the study, it is believed that internal innovative capabilities of firms have a prominent rule in facilitating IT diffusion. This factor is made up of three proxy variables: level of IT knowledge, level of IT investment and coherent IT strategy reflecting the circumstances by which small and medium-sked firms are able to respond to possible technological changes. The existence of government support is also a contributing factor to the diffusion and adoption of IT. However, weak relationship between the institutions and industry groups could inhibit the diffusion and adoption of IT within firms.